INSTITUSIONALISASI HOME SCHOOLING DI INDONESIA: IMPLIKASI TERHADAP PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM DI EL-DINA HOME SCHOOLING CENTRE - Suparjo Suparjo (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
The background of this study lies in the need for an inclusive, holistic, and innovative educational approach that integrates Islamic values comprehensively. This research aims to investigate the implications of institutionalizing home schooling on the development of Islamic education curriculum in Indonesia, with a focus on El-Dina Home Schooling Centre in Purwokerto. The research methodology employed a qualitative approach, using interviews and observations with students, parents, and teachers at El-Dina. The findings reveal that El-Dina implements an approach that emphasizes the uniqueness of students' characteristics, actively involves parents in the educational process, and integrates Islamic education holistically into their curriculum. The research concludes that the institutionalization of home schooling in El-Dina provides a positive contribution to the development of Islamic education in Indonesia by creating an effective and enjoyable learning environment. The implications and novelty of this research lie in providing guidance for the development of inclusive, holistic, and innovative Islamic education in Indonesia. In conclusion, this study highlights the potential of institutionalized home schooling to bring about positive changes in the development of Islamic education by considering students' uniqueness and actively engaging parents in the educational process.